Dutch disease and the mitigation effect of migration: Evidence from Canadian provinces - Michel Beine; Serge Coulombe; Wessel N. Vermeulen (Center for Economic Studies and ifo Institute (CESifo), 2012)
This paper looks at whether immigration can mitigate the Dutch disease effects associated with booms in natural resource sectors. We first derive predicted changes in the size of the non-tradable sector from a small general-equilibrium model à la Obstfeld-Rogoff, supplemented by a resource income and a varying labour supply. Using data for Canadian provinces, we test for the existence of a mitigating effect of immigration in terms of an increase in the size of the non-tradable sector triggered by the positive resource shock in booming regions. We find evidence of such an effect for the aggregate inflow of migrants. Disentangling those flows by type of migrants, we find that the mitigation effect is due mostly to interprovincial migration and temporary international migration. There is no evidence of such an effect for permanent international immigration. Nevertheless, interprovincial migration also results in a spreading effect of Dutch disease from booming to non-booming provinces.
Keywords: F22; O15; R11; R15; 330; natural resources; Dutch disease; immigration; mitigation effect